2006
DOI: 10.1038/sj.ejcn.1602571
|View full text |Cite
|
Sign up to set email alerts
|

Development of a tomato-based food for special medical purposes as therapy adjuvant for patients with HCV infection

Abstract: Objective: The present study aimed to develop a food for special medical purposes (FSMP) and to assess its efficacy as adjuvant therapy in patients with chronic hepatitis C virus (HCV). Design: Open randomized clinical trials with a tomato-based FSMP used as adjuvant treatment to the pharmacological therapy with pegilated interferon and ribavirin. Subjects: Eight healthy volunteers and 39 HCV patients. Interventions: For the bioavailability study, healthy subjects consumed 100 g/die FSMP for a week and their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Nevertheless, some studies have already reported an improvement in patients infected by HCV with supplements of zinc,[13] vitamin E and C [27] among other nutrients. [28]…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some studies have already reported an improvement in patients infected by HCV with supplements of zinc,[13] vitamin E and C [27] among other nutrients. [28]…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged heating of whole tomatoes, including their seeds and skins, maximized the concentration of flavonoids and carotenoids (21) and promoted the formation of ketosamine (14).…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoid determination, extraction and high-performance liquid chromatography analysis of sera, and serum flavonoid extraction and high-performance liquid chromatography/ tandem mass spectrometry analysis of the extracts were done as previously described (21,22). The ferric-reducing ability of plasma was assayed according to the original description (23).…”
Section: Serum Protein Analysismentioning
confidence: 99%
“…Also, in an in vitro study, HCV proliferation was markedly suppressed by treatment with PUFAs, such as arachidonic acid, eicosapentaenoic acid, and docosahexaenoic acid [48, 49]. Additionally, it has been reported that   β -carotene-containing food and herbal food show an adjuvant effect for IFN-based antiviral therapy [50, 51]. Accordingly, these nutrients are expected to be used as adjuvants in antiviral therapy for patients with HCV infection.…”
Section: Nutrition Therapy For Chc Patientsmentioning
confidence: 99%